Single-cell sequencing reveals the role of SALL4 in cervical cancer development - Bao Tonghui; Li Wufen; Qi Lin (BMC Cancer)
Abstract Objective This study aims to investigate the role of SALL4 in the development and progression of cervical cancer, particularly its impact on the proliferation, migration and adhesion of HeLa cells, and to explore the clinical potential of SALL4 as a therapeutic target. Methods Single-cell sequencing technology was utilized to analyze the cellular characteristics of cervical cancer tumor cell populations, and transcriptomic data were integrated to assess the differential expression of SALL4. Additionally, both in vitro and in vivo experiments were conducted to evaluate the effects of SALL4 inhibition on cell proliferation, migration, adhesion, and its regulation of collagen content and fibrosis. Results High expression of SALL4 significantly promoted the proliferation, migration, and adhesion of cervical cancer cells. After SALL4 knockout, the migration and proliferation rates were significantly lower than those of HeLa cells. Immunofluorescence and in vivo experiments showed that SALL4 knockout cells exhibited a significantly reduced tumor formation ability, with lower proliferation and fibrosis levels compared to HeLa cells. Conclusion High expression of SALL4 promotes cervical cancer progression, while inhibition of SALL4 expression effectively suppresses cancer development. As a critical regulatory factor, SALL4 has the potential to become a therapeutic target for cervical cancer, and its application in cervical cancer treatment warrants further exploration.